Strategic co-location in a hybrid process involving desalination and Pressure Retarded Osmosis (PRO) - Sim, Victor S. T. (2013)
This paper focuses on a Hybrid Process that uses feed salinity dilution and osmotic power recovery from Pressure Retarded Osmosis (PRO) to achieve higher overall water recovery. This reduces the energy consumption and capital costs of conventional seawater desalination and water reuse processes. The Hybrid Process increases the amount of water recovered from the current 66.7% for conventional seawater desalination and water reuse processes to a potential 80% through the use of reclaimed water brine as an impaired water source. A reduction of up to 23% in energy consumption is projected via the Hybrid Process. The attractiveness is amplified by potential capital cost savings ranging from 8.7%–20% compared to conventional designs of seawater desalination plants. A decision matrix in the form of a customizable scorecard is introduced for evaluating a Hybrid Process based on the importance of land space, capital costs, energy consumption and membrane fouling. This study provides a new perspective, looking at processes not as individual systems but as a whole utilizing strategic co-location to unlock the synergies available in the water-energy nexus for more sustainable desalination.